Reproductive Tissue Storage: Quality Control and Management/Inventory Software - Pomeroy, Kimball O.; Marcon, Mark (Seminars in Reproductive Medicine, 2018)
The recent failure of two liquid nitrogen storage tanks at two separate facilities in the United States has highlighted the need to reexamine our approach to how reproductive laboratories handle the storage of tissue. If we wish to truly understand how we can increase the security and safety of stored reproductive tissue, we really need to understand how often these events (tank failure) occur and what are the ultimate causes of these failures. Are there design flaws in the storage tanks or are these really failures in protocols and following protocols? Unfortunately, because these cases often involve serious litigation, most do not want to or are forbidden to talk about these failures and so we have little data to base recommendations on. Despite the paucity of data, we must come up with protocols and methods to safeguard tissue stored in these tanks. At the same time, we must be careful that we do not introduce potential solutions to these problems that instead of increasing the safety of stored tissue, we exacerbate the problem. Attention should be paid to where tanks are located so that they can be observed throughout the day. Decisions regarding whether tissue will be stored on-site or off-site, whether small- or large-capacity tanks should be used, or whether a patient's specimens should be split among several tanks should not be based on convenience or cost, but on the ability to reduce risks to these precious specimens. Ongoing quality control (QC) must include checking tanks for both visual clues and analyzing evaporation rates of each tank. Finally, each laboratory must have protocols in place that address all the issues involved in maintaining a safe storage system. These protocols must be understood by all those involved in the safeguard of patients' tissue. We may never eliminate all accidents with stored reproductive tissue, but we can reduce the probability of future accidents. In this article, we will discuss how to manage the risks inherent with the storage of reproductive tissue, where to store tissue, how to store them, how to reduce risks through quality control methods, and finally, options available for inventory management.
Keywords: IVF; storage; liquid nitrogen; quality control; software